Persepsi Mahasiswa Dalam Penggunaan Aplikasi Berbasis Text to Speech Pada Mata Kuliah Teknologi Pembelajaran Bahasa Arab - Muhammad Husni Mubarak; Agung Budi Santoso (IAIN Manado, 2023)
Student Perceptions in the Use of Text to Speech-Based Applications in Arabic Learning Technology Courses. This study investigates students' perceptions of the use of text-to-speech applications in Arabic language learning technology courses in a descriptive quantitative manner. The method employed is quantitative, involving the completion of a questionnaire and the use of a data processing technique in the form of quantitative descriptive analysis. This study's participants were students who had taken the Arabic Language Learning Technology course. Using a SWOT analysis, the text to speech application chosen in this study is narakeet.com. In this study, data was collected using a Likert scale questionnaire with five alternative answers and three assessment indicators, namely the perception of the application's design, function, and ease of use. The majority of students agree with the answer, and the findings of this study show that students' perceptions of the use of text-to-speech applications naraaket.com fall into a fairly good category